Desplazamientos léxico-semanticos y efectos macroestructurales en la traducción española de The Alexandria Quartet. Topología Conceptual - Sánchez García, Jesús M. (Miscelánea: A Journal of English and American Studies, 1995)
The article is part of a research effort which develops a combined functional lexically-oriented methodology within Descriptive Translation Studies designed to examine lexico-semantic and macrostructural, i.e. thematic, shifts in translated narrative texts such as the Spanish translation of Lawrence Durrell's The Alexandria Quartet to which the methodology has been applied with reference to the theme of love. It explores the role that specifying the lexico-conceptual domains of the units in lexico-semantic shifts play in interpreting transemes (textual units in a translational relation) as well as in obtaining a general conceptual structure for the text analysed which may ultimately lead to a statement on the transemic macrostructure for a given topic. Besides, it provides some specific results as to the love-related transemic macrostructure for The Quartet and its Spanish translation, which we have been able to derive by applying our methodology.